Utility of geo-informatics for disaster risk management:Linking structural damage assessment, recovery and resilience: powerpoint - Kerle, N. (University of Twente, 2020)
This lecture pesents some problem: Image-based damage mapping; Limits of vertical imagery and prospect of oblique data; Prospect of crowdsourcing; Lack of coordination and user needs understanding; What comes after a disaster – tracking recovery; Linking recovery and resilience.